Hot Carrier Effect in Single Injection Diode with Thermal Free Carriers - Sharma Y.K.; Srivastava B.B. (My University, 2025)
Expressions for the noise temperatures in a single injection solid state diode operating in the hot carrier regime are given for the space‐charge and ohmic region separately. The method of regional approximation is used to separate the insulator into two regions. It is shown that the difference between the noise temperature and lattice temperature in the case of the insulator with thermal free carriers is always less than the value calculated in the absence of thermal free carriers. Copyright © 1975 Wiley‐VCH Verlag GmbH & Co. KGaA